LA REELECCIÓN PRESIDENCIAL EN LATINOAMÉRICA, UN FENÓMENO QUE AFECTA LA DEMOCRACIA REPUBLICANA (2016)
Warlordism is the political regime that characterizes Latin American political culture for which from the point of view of democracy has been established re-election as a way to keep the detriment of republican democracy should be ensured that limit the exercise of presidential power a reasonable period without re-election to strengthen political parties that invigorate democracy